A narrative approach in evaluation: "Narratives of Change" method. (14th November 2016) - Baú, Valentina
Abstract : Purpose: The purpose of this paper is to introduce the new qualitative method of "Narratives of Change" to evaluate a project's impact. This new methodology arises from a combination of the most significant change technique with a narrative analysis approach, and it is suitable for community development interventions. Design/methodology/approach: Narrative approaches are seldom used in programme evaluation. However, depending on the nature and context of a project, it might be useful to offer a space for people to tell their story. Asking people to recognise change by recounting the passage from their previous to their present situation can help the researcher grasp particular concepts that may otherwise not be visible. At the same time, while the analysis of in-depth interviews can be difficult and time consuming, the method introduced here simplifies this process by offering a tool that allows the researcher to extrapolate semantic fragments from long interviews and facilitates the identification of prototypical characters in each narration. Findings: After offering a theoretical discussion that introduces this technique, its practical illustration and the example presented in this paper show how this method represents a useful instrument for participants' stories analysis in qualitative project evaluations aimed at identifying change. Originality/value: This paper introduced a new qualitative method to carry out a programme evaluation using narrative analysis.